Efficacy and safety of concomitant immunotherapy and denosumab in patients with advanced non-small cell lung cancer carrying bone metastases: A retrospective chart review - Li, Hong-Shuai; Lei, Si-Yu; Li, Jun-Ling; Xing, Pu-Yuan; Hao, Xue-Zhi; Xu, Fei; Xu, Hai-Yan; Wang, Yan (Frontiers in Immunology, 2022)
Background Synergistic anti-tumor effects were observed in vivo and in vitro when immune checkpoint inhibitors (ICIs) were combined with denosumab. However, the clinical benefit and safety of this synergy have not been adequately evaluated in non-small cell lung cancer (NSCLC). Methods Consecutive charts of NSCLC patients with bone metastases between December 2020 and December 2021 in the Chinese National Cancer Center were reviewed. The entire cohort was divided into one experimental group (denosumab + ICIs [DI]) and three control groups (denosumab + non-ICIs [DnI], phosphates + ICIs [PI], phosphates + non-ICIs [PnI]). Real-world objective response rates (ORRs), median progression-free survival (mPFS), skeletal-related events (SREs), and adverse events (AEs) were compared between groups. Results A total of 171/410 (41.7%) patients with advanced or recurrent NSCLC carrying bone metastases who received bone-targeted therapy were eligible for analysis. Although the DI group showed a better benefit trend, differences were not statistically significant concerning the therapeutic efficacy among the DI group (n = 40), PI group (n = 74), DnI group (n = 15), and PnI group (n = 42) (ORRs: 47.5%, 43.2%, 33.3%, and 40.5%, respectively, p = 0.799; and mPFS: 378, 190, 170, and 172 days, respectively, p = 0.115; SREs: 5%, 10.8%, 13.3%, and 11.9%, respectively, p = 0.733). Nevertheless, further analysis in the NON-DRIVER cohort revealed a greater benefit for the DI group (p = 0.045). Additionally, the AEs of the DI group were not significantly different from those of the PI, DnI, and PnI groups (AEs: 27.5%, 39.2%, 26.7%, and 28.6%, respectively, p = 0.742). Furthermore, the multivariate analysis revealed the independent prognostic role of DI treatment for PFS in the overall cohort. Within the DI group, we did not observe differences in benefit among different mutational subgroups (p = 0.814), but patients with single-site bone metastasis (p = 0.319) and high PD-L1 expression (p = 0.100) appeared to benefit more, though no significant differences were observed. Conclusions Denosumab exhibited synergistic antitumor efficacy without increasing toxicity when used concomitantly with ICIs in patients with advanced non-small cell lung cancer carrying bone metastases.